“The role of T cell receptor signaling thresholds in guiding T cell fate decisions” - Zikherman, Julie (Curr Opin Immunol, 2015)
Canonical T cell receptor signal transduction has been extensively studied and dissected in cell lines and primary lymphocytes. However, a static depiction of this signaling cascade fails to capture the complex and dynamic process by which individual T cells discriminate TCR:peptide-MHC affinity, then integrate signals over time to drive discrete cellular behaviors such as thymic selection, proliferation, and cytokine production. Recent technological advances have made it possible to study complex lymphocyte behavior on a single cell level and are revealing how T cells interpret information about affinity and abundance of antigen in order to make life-and-death cell fate decisions individually and collectively.